The Dynamics of Spatial Structure and Spatial Pattern Changes at the Fringe Area of Makassar City - Batara Surya (Indonesian Journal of Geography, 2015)
The study is conducted at the fringe area of Makassar City by analyzing dynamics of spatial structure and spatial pattern changes at the fringe area of Makassar City. It applies quantitative and qualitative approaches (mixed method). Data is acquired from some sources and informants living at the fringe area of Makassar City. Spatial utilization shift and development of transport infrastructure, especially for main road corridor connecting down town of Makassar City and fringe area, affect significantly spatial structure and spatial pattern changes at the fringe area of  Makassar City. Dynamics of spatial structure and spatial pattern changes contributes changes of resident mobility; while, development tendency of the existing spatial and land use is no longer determined based on productivity, but it is valued by functions of space and land at the fringe are of Makassar City.